Unpacking the complexities of teacher identity: Narratives of two Chinese teachers of English in China. (July 2022) - Li, Wendy
This study explores the complexities of teacher identity formation for two Chinese teachers of English in China, who represent two growing groups of English teachers: Alice, who worked in a private English training institution and John, who was a self-employed private English tutor. Drawing insights from Barcelos' (2015) theorization of the relationship among teacher beliefs, teacher identity, and teacher emotions, this study employs an integrated perspective to investigate two participants' English teacher identity development by examining the dynamic interplay among these three constructs (beliefs, identity, and emotions). Narrative inquiry is used for data analysis. By exploring two participants' life histories of learning English and becoming English teachers, this study captures the dynamics of how the focal participants' core beliefs and emotions interacted inextricably with and shaped their teacher identity development.